Types of Attractive Dosage Forms for Primary School Students and Associated Factors in Baghdad/ Iraq - Sura Zuhair Mahmood; Nora Zawar Yousif; Zeina Dawood Salman (College of Pharmacy / Mustansiriyah University, 2022)
The lack of age-appropriate and child -friendly formulation of medication for children poses a major challenge to pediatric therapeutic practice, adherence, and health care delivery worldwide, however, formulation acceptability and preferences facilitate medication   adherence in children, and they are important factors in achieving the intended treatment outcomes in which this study looks ahead. The present study aims to determine the various medication trends of children through their parents and caregivers, child preference of certain dosage form (chewable gel) in comparison with another solid dosage forms and its popularity among Iraqi primary school, furthermore the study highlights different variables influence student preference for chewable gel.  A total of 230 Iraqi primary school students were randomly selected and interviewed with the presence of their parents. It was observed that (51.3%) of the parents/caregivers reported that the liquid dosage form is the most dosage form that commonly used, (72%) of consumers revealed that the capsules and tablets are not easy to swallow, furthermore,   this study revealed that (68.6%)  of school students preferred to take medication as chewable gel over than other oral solid dosage forms ,and this preference varied significantly with several socioeconomic and other factors.